Efektivitas Giberelin Acid (GA3) Terhadap Pertumbuhan Kecambah Kopi Robusta (Coffea canephora) - Rio Stepanus Tarigan; Angela Septryani Saragih (Cattleya Darmaya Fortuna, 2026)
The germination of Coffea canephora (robusta coffee) seeds generally occurs slowly due to their hard seed coat, which inhibits the absorption of water and oxygen. One effort to accelerate germination and improve early seedling growth is the application of the plant growth regulator gibberellic acid (GA3). This study aimed to determine the effectiveness of various concentrations of GA3 on the growth of robusta coffee seedlings. The research was conducted from November 2025 to January 2026 using a non-factorial Randomized Complete Block Design (RCBD) with four treatments: G0 (control without GA3), G1 (2 mg L⁻¹), G2 (3 mg L⁻¹), and G3 (4 mg L⁻¹), each replicated four times. Coffee seeds were soaked in GA3 solution for 24 hours prior to sowing. The observed parameters included germination percentage, germination rate, hypocotyl length, plant height, root length, and number of leaves. The results showed that GA3 application significantly enhanced the growth of robusta coffee seedlings compared to the control, including improvements in plant height, leaf number, hypocotyl length, root length, germination rate, and germination percentage. GA3 treatment accelerated the breaking of seed dormancy, resulting in earlier seedling emergence compared to the control. Although GA3 application consistently improved all observed growth parameters, no statistically significant differences were found among the GA3 concentrations (G1, G2, and G3). The application of GA3 increased seed viability, as indicated by a higher percentage of germinated seeds compared to the control.